Incidence and Risk Factors for Hospital Readmission or Unexpected Visits in Women Undergoing Unscheduled Cesarean Delivery - La Rosa, Mauricio; Jauk, Victoria; Saade, George R.; Boggess, Kim; Longo, Sherri; Clark, Erin A. S.; Esplin, Sean; Cleary, Kirsten; Wapner, Ronald; Letson, Kellet; Owens, Michelle Y.; Blackwell, Sean; Szychowski, Jeff M.; Andrews, William; Tita, Alan T.; for the Cesarean Section Optimal Antibiotic Prophylaxis Trial Consortium (American Journal of Perinatology, 2019)
Objective Hospital readmissions are increasingly tracked and assessed for value-based compensation. Our objective was to determine the incidence and risk factors associated with post-cesarean delivery (CD) readmissions or unexpected visits, defined as unexpected office or emergency room visits.Study Design This is a secondary analysis of a multicenter randomized controlled trial of adjunctive azithromycin prophylaxis for CD performed in laboring patients with viable pregnancies. Patients were followed up to 6 weeks postpartum. Our primary outcome was a composite of hospital readmission or unexpected visit, defined as unscheduled clinic or emergency department visits. Data of hospital readmissions, unexpected visits, and their reasons were collected. Demographics, antepartum, intrapartum, and postpartum risk factors were evaluated in bivariate analyses and multivariable logistic regression modeling.Results A total of 1,019 women were randomized to azithromycin and 994 to placebo. The prevalence of readmission or unexpected visit was 10.2% (95% confidence interval [CI]: 8.9–11.6), with rates of 3.8% (95% CI: 3.0–4.7%) hospital readmissions, 6.9% (95% CI: 5.8–8.0%) emergency room visits, and 4.2% (95% CI: 3.4–5.2%) unexpected clinic visits. The most common causes were infectious disease and hypertensive disorder. Women with readmissions or unexpected visits were more likely to be obese and diabetic, as well as experience longer length of ruptured membranes, intrauterine pressure catheter placement, and postpartum fevers. On multivariable analysis, diabetes (adjusted odds ratio [aOR]: 1.6, 95% CI: 1.1–2.4), prolonged ruptured membranes (aOR: 1.9, 95% CI: 1.3–2.8), and postpartum fevers (aOR: 4.6, 95% CI: 3.0–7.0) were significantly positively associated with readmission or unscheduled visit, while azithromycin was a protective (aOR: 0.6, 95% CI: 0.5–0.9).Conclusion Women who had postpartum fever were at especially high risk for readmission or unexpected visits. Diabetes, prolonged ruptured membranes, and postpartum fevers were significantly associated with the adverse outcome, and azithromycin was associated with lower rates of readmission and unexpected visits.
Keywords: cesarean; readmission; pregnancy